2016
DOI: 10.14748/ssmd.v1i1.1684
|View full text |Cite
|
Sign up to set email alerts
|

Linear and volumetric assessment of the maxillary sinus

Abstract: INTRODUCTION: Pneumatization of the maxillary sinus can be triggered throughout a patient's life. Prior to any sinus floor augmentation procedure, it is imperative to conduct a linear and volumetric assessment of the maxillary sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The results of our study also confirm this fact as there was no statistically significant difference in the linear and volumetric measurements except in linear measurement (craniocaudal) between the 1st and 2nd molar teeth. However, a study by Georgiev et al [ 21 ] has revealed a statistically significant difference in favor of male patients in their analysis of volumetric measurements across genders.…”
Section: Discussionmentioning
confidence: 97%
“…The results of our study also confirm this fact as there was no statistically significant difference in the linear and volumetric measurements except in linear measurement (craniocaudal) between the 1st and 2nd molar teeth. However, a study by Georgiev et al [ 21 ] has revealed a statistically significant difference in favor of male patients in their analysis of volumetric measurements across genders.…”
Section: Discussionmentioning
confidence: 97%